Penerapan Konsep Neo-Vernakular Suku Tengger dalam Redesain Pasar Pasrepan - Prahmana, Sendi; Hersanyo, Benny Bintarjo Dwinugroho; Panjaitan, Tigor Wilfritz Soaduon (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2025)
Neo-Vernacular architecture, as a response to rigid modernism, offered a more holistic approach to building design. This concept integrates traditional, cultural and environmental values ​​into modern design. This research aims to apply the Neo-Vernacular concept of the Tengger Tribe in the redesign of Pasrepan Market. Pasrepan Market, as the center of economic and social activity for the Tengger community, has great potential to become a unique tourist icon. By adopting the roof shape of a traditional Tengger house combined with modern materials such as light steel, this market design not only respects cultural heritage, but also increases the efficiency and durability of the building. Apart from that, the use of typical Tengger batik ornaments on the building facade further strengthens local identity and creates a distinctive atmosphere. It is hoped that this research can become a reference in creating buildings that are not only aesthetic, but also environmentally friendly and uphold local cultural values. By combining traditional and modern elements in the redesign of Pasrepan Market, it is hoped that it can become an example for the sustainable development of other traditional markets. Kata kunci: Neo-Vernacular Architecture, Tengger Tribe, Pasrepan Market, redesign, local culture, cultural heritage, tourism.